Modification method of copper-based catalyst for electrocatalytic reduction of carbon dioxide as well as product and application of copper-based catalyst

By preparing a specific solution to treat copper-based materials, nano cuprous oxide catalysts are solved, and the problems of complex preparation, high cost and insufficient stability of copper-based catalysts in the prior art are achieved, and high efficiency and selectivity are achieved. It is suitable for Mass production and long-term operation.

CN119194493APending Publication Date: 2024-12-27WESTLAKE UNIV +1

Patent Information

Application Number
CN202411453899.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The copper-based catalyst used for electrocatalytic carbon dioxide reduction in the prior art is difficult to be simple, fast, safe, suitable for large-scale production, cheap, high selectivity, can operate at a high current density, and operate for a long time, and has high cost. , problems such as complex preparation methods and insufficient stability.

Method used

By preparing a first solution containing copper ions and halogen ions and a second solution of hydroxide ions, the copper-based material is processed respectively to generate copper halide and copper oxide, so as to achieve in-situ preparation of nanocubic acid for high efficiency Reduce carbon dioxide or carbon monoxide to form a catalyst with high selectivity, stable structure and stable long-term operation.

Benefits of technology

It achieves high selectivity and efficient carbon dioxide or carbon monoxide reduction. The catalyst has good structural stability and high current operation ability. It is suitable for large-scale production, with low cost, high safety and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194493A_ABST
    Figure CN119194493A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of electro-catalysis, and particularly relates to a modification method of a copper-based catalyst for electro-catalysis carbon dioxide reduction and a product and application of the copper-based catalyst. The modification method comprises the following steps: (1) respectively preparing a first solution containing copper ions and halogen ions and a second solution containing hydroxyl ions; (2) putting the copper-based material into the first solution, reacting, generating a cuprous halide phase on the surface of the copper-based material, and taking out the copper-based material; and (3) putting the copper-based material taken out in the step (2) into the second solution, and reacting to generate cuprous oxide in situ. According to the method, a copper-based material is subjected to a neutralization reaction to generate cuprous chloride, and then a reconstruction reaction is performed to generate cuprous oxide, so that in-situ preparation of the high-adaptability nano cuprous oxide particles is successfully realized, and the cuprous oxide can be used for efficiently reducing carbon dioxide or carbon monoxide into a multi-carbon product; and high selectivity, good structural stability, long-time operation stability and large-current operation capability are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrocatalysis, and in particular relates to a modification method of a copper-based catalyst for electrocatalytic carbon dioxide reduction, and a product and application thereof. Background Art

[0002] Intermittent renewable energy sources such as wind, solar and tidal energy are unstable and the electricity they produce must be used immediately or stored. Although a variety of energy storage technologies are available, such as pumped storage, compressed air, batteries, flow batteries and flywheels, they have certain limitations in terms of scale, applicability or maximum storage period. The carbon dioxide reduction reaction can utilize these intermittent renewable energy sources on a large scale, converting carbon dioxide into products with a higher degree of reduction, and storing electricity in reduction products with higher energy density and wider applicability, storing renewable energy on a large scale in the form of chemical products.

[0003] Electrocatalytic CO2 reduction, as a method for converting CO2 into high-value-added chemicals and fuels, can not only reduce greenhouse gas emissions, but also contribute to the production of sustainable fuels and the efficient storage of intermittent renewable energy. Compared with other chemical reduction pathways for CO2, electrocatalytic methods have the following very significant characteristics. First, electrocatalytic CO2 reduction methods can convert electrical energy from intermittent renewable energy sources into chemical energy and store it in chemical feedstocks or fuels. Second, the reaction conditions are mild and can usually be operated at room temperature or near room temperature and ambient pressure. Third, the reduction products can be adjusted by changing additional parameters such as catalysts, electrolytes, and applied voltage.

[0004] Activating CO2 molecules requires a large overpotential, which leads to low energy efficiency. In addition, the reduction of CO2 is a highly complex process, with both gas and liquid products, both products containing one carbon and multi-carbon products, and both 2-electron transfer products and 18-electron transfer products, such as carbon monoxide, formic acid, methanol, methane, acetic acid, ethylene, ethanol and n-propanol. These products have similar thermodynamic redox potentials, resulting in poor selectivity for specific products. In addition, electrocatalytic CO2 reduction can obtain the same product through multiple pathways, which poses a huge challenge to how to achieve high selectivity for the desired specific product. At the same time, the potential of the representative competitive reaction of CO2 reduction, the hydrogen evolution reaction (HER), is similar to that of the CO2 reduction reaction. The hydrogen intermediate (*H) required for the hydrogen evolution reaction is more stable than the carbon monoxide intermediate (*CO) and carboxyl intermediate (*COOH) required for CO2 reduction, which makes the hydrogen evolution reaction dominant at higher overpotentials, reducing the selectivity and efficiency of the CO2 reduction reaction. Designing and screening ideal catalysts that have high activity for CO2 reduction and effectively inhibit the hydrogen evolution reaction is an important research direction.

[0005] Before electrocatalytic CO2 reduction can be applied in practice, significant barriers related to energy efficiency and selectivity must be overcome. Therefore, it is urgent and challenging to develop some low-cost catalysts to drive the CO2 reduction process with high energy efficiency and selectivity.

[0006] Copper-based catalysts are the most promising and efficient materials for reducing carbon dioxide to multi-carbon products. The high selectivity of copper-based catalysts for multi-carbon products including ethylene, ethanol and n-propanol has been demonstrated. Many experimental reports have shown that oxide-derived copper catalysts have higher selectivity for multi-carbon products. Some experiments and theoretical calculations have also shown that monovalent copper (Cu 1+ ) and zero-valent copper (Cu 0 ) coexistence (Cu δ+ ,0<δ<2) is conducive to the adsorption of carbon monoxide intermediates, thereby promoting the dimerization of carbon monoxide intermediates and leading to the formation of carbon-carbon bonds. By improving the structure of copper-based catalysts and the design of gas diffusion electrodes (GDEs), it has been possible to achieve a high conductivity at over 200 mA cm -2 The selectivity of multi-carbon products exceeded 80% at a practical current density of 1.34 W·m- ...

[0007] In the prior art, when preparing copper-based catalysts, some methods use precious metal compounding, compounding with other metals to form alloys, plasma sputtering or electrodeposition, etc. These methods all have some defects to varying degrees, such as a large number of synthetic raw materials, complex preparation methods, and lengthy steps.

[0008] For example, Chinese patent document CN116590775A discloses a method for preparing a copper-based nanomaterial rich in two-dimensional defects and its application in electrocatalytic CO2 reduction. The method uses an electrochemical deposition method, which is not suitable for large-scale use. The use of pure copper foil as the anode leads to high costs. In addition, since the electrochemical deposition method does not form the catalytic active sites in situ, there are problems such as catalyst shedding, catalytic site deactivation, or long-term operating stability that needs to be confirmed.

[0009] Chinese patent document CN116288474A discloses a method for preparing a CuO@Cu2O composite catalyst for electrocatalytic reduction of carbon dioxide to ethylene. The preparation method requires the use of reagents such as copper chloride, polyvinyl pyrrolidone, sodium hydroxide, ascorbic acid, ethanol, etc. The reagents are of many types and are relatively expensive. In addition, the reaction is required to be carried out under high temperature and high pressure, and the conditions are harsh.

[0010] Chinese patent document CN116005195A discloses a gas-assisted synthesis method of microcrystalline cuprous oxide electrocatalyst and its application. This method firstly requires the introduction of exogenous gas, which makes the synthesis method complicated and has high requirements on the device. Secondly, high-purity air and high-purity argon are difficult to obtain and are expensive, which makes the method uneconomical.

[0011] Chinese patent document CN115852485A discloses a graded tip cuprous oxide single crystal material and its preparation method and application. Although this method can achieve good selectivity of reducing carbon dioxide to multi-carbon products at a relatively low overpotential, the reaction time of this method is relatively long and the method is lengthy and cumbersome.

[0012] Therefore, it is of great significance to develop a copper-based catalyst for electrocatalytic carbon dioxide reduction that is simple, fast, safe, suitable for large-scale production, inexpensive, highly selective, and capable of operating at high current density and for a long time. Summary of the invention

[0013] Therefore, the technical problem to be solved by the present invention is to overcome the defects of the copper-based catalysts used for electrocatalytic carbon dioxide reduction in the prior art, such as difficulty in being simple, rapid, safe, suitable for large-scale production, cheap, highly selective, capable of operating at high current density and for a long time, thereby providing a copper-based catalyst for catalytic reduction and its preparation method and application.

[0014] To this end, the present invention provides the following technical solutions.

[0015] The first aspect of the present invention provides a method for modifying a copper-based catalyst for electrocatalytic carbon dioxide reduction, comprising the following steps:

[0016] (1) preparing a first solution containing copper ions and halogen ions and a second solution containing hydroxide ions respectively and setting them aside;

[0017] (2) placing a copper-based material into a first solution to react, generating a cuprous halide phase on the surface of the copper-based material, and taking out the copper-based material;

[0018] (3) The copper-based material taken out in step (2) is placed in the second solution to react and generate cuprous oxide in situ.

[0019] In the present invention, the first solution contains copper ions and halogen ions; further, the first solution may also contain other ions, such as sodium ions, sulfate ions, and the like.

[0020] There is a zero-valent copper phase on the surface of the copper-based material;

[0021] Preferably, the copper-based material is copper foil, copper sheet or copper powder;

[0022] Preferably, the copper powder is at least one of copper nanotubes, copper nanospheres and copper nanorods.

[0023] In the present invention, when the copper-based material is a copper sheet or copper foil, the copper-based material is first cleaned. The cleaning method may be, but is not limited to: a two-electrode system using a platinum electrode as a counter electrode and a reference electrode, with the copper-based material as an anode, and the copper-based material is electropolished in an 85% phosphoric acid solution. As long as the oxide on the surface of the copper-based material can be removed, there is no requirement for the applied voltage. Then, the copper-based material is thoroughly rinsed with deionized water or ultrapure water and dried with nitrogen. It should be noted that the drying step can be omitted, but step (2) needs to be performed as soon as possible.

[0024] In the present invention, when the copper-based material is copper powder, such as copper nanotubes, copper nanospheres or copper nanorods, polishing treatment is not required before the reaction, because divalent copper will undergo a weak hydrolysis reaction. The specific reaction equation is as follows: Make the first solution weakly acidic, and the following reaction will occur automatically: CuO·xCu2O+2(x+1)H + =xCu 0 +(x+1)Cu 2+ +(x+1)H2O, according to the principle of chemical equilibrium, the first reaction moves to the right to remove the oxide on the surface of the copper-based material. Therefore, there is no need to polish the copper powder.

[0025] In the step (3), the reaction is carried out until the surface of the copper-based material turns yellow, and cuprous oxide is generated in situ.

[0026] The halogen ion is at least one of a chloride ion and a bromide ion;

[0027] Preferably, the first solution includes at least one of a copper salt and a halide, ensuring that the first solution contains both copper ions and halide ions;

[0028] Preferably, the copper salt is at least one of copper sulfate, copper nitrate, copper chloride and copper bromide;

[0029] Preferably, the halide is at least one of sodium chloride, potassium chloride, sodium bromide, potassium bromide, copper chloride and copper bromide;

[0030] Preferably, the first solution is at least one of copper chloride and copper bromide.

[0031] The second solution includes at least one of a strong base, a weak acid salt and a base, ensuring that the second solution contains hydroxide ions;

[0032] Preferably, the strong base weak acid salt is at least one of potassium bicarbonate, potassium carbonate, sodium bicarbonate, sodium carbonate, potassium acetate and sodium acetate;

[0033] Preferably, the base is at least one of sodium hydroxide and potassium hydroxide.

[0034] When the second solution is a strong base and a weak acid salt, the concentration of the second solution is 0.01 mol / L to 1 mol / L;

[0035] Preferably, when the second solution is alkaline, the pH of the second solution is ≥12.

[0036] In the present invention, the second solution contains hydroxide ions; further, the hydroxide ions may be hydroxide ions generated by hydrolysis of a strong base and a weak acid salt, for example, bicarbonate ions are hydrolyzed in water to generate hydroxide ions. As long as the second solution contains hydroxide ions, the source of the hydroxide ions is not specifically limited.

[0037] The molar ratio of copper ions to halogen ions in the first solution is (1-10):(1-10);

[0038] Preferably, the concentration of copper ions in the first solution is 0.01 mol / L to 1 mol / L;

[0039] Preferably, the concentration of halogen ions in the first solution is 0.01 mol / L to 1 mol / L.

[0040] The second aspect of the present invention provides a copper-based catalyst prepared by the above modification method.

[0041] A third aspect of the present invention provides a method for catalytic reduction of carbon dioxide, using the copper-based catalyst prepared by the above modification method.

[0042] A fourth aspect of the present invention provides a method for catalytic reduction of carbon monoxide, using the copper-based catalyst prepared by the above-mentioned modification method.

[0043] The technical solution of the present invention has the following advantages:

[0044] 1. A modification method for a copper-based catalyst for electrocatalytic carbon dioxide reduction provided by the present invention comprises: (1) preparing a first solution containing copper ions and halogen ions and a second solution containing hydroxide ions respectively, and preparing them for standby use; (2) placing a copper-based material in the first solution, reacting, generating a cuprous halide phase on the surface of the copper-based material, and taking out the copper-based material; (3) placing the copper-based material taken out in step (2) in the second solution, reacting, and generating cuprous oxide in situ. The method first allows the copper-based material to undergo a neutralization reaction in the first solution to generate cuprous chloride, and then undergoes a reconstruction reaction in the second solution to generate cuprous oxide, thereby successfully achieving the in-situ preparation of highly adaptable nano cuprous oxide particles, which can be used to efficiently reduce carbon dioxide or carbon monoxide to multi-carbon products, and has high selectivity, good structural stability, long-term operation stability, and high current operation capability. The preparation method has the advantages of fast reaction kinetics, few types of raw materials, low raw material cost, applicability to large-scale production, high safety, and environmental friendliness.

[0045] The preparation method produces cuprous oxide nanoparticles, which are regular and cubic in shape, evenly distributed on the surface and highly covered. The formed particle surface has abundant monovalent copper ion sites and more crystal defects, which further indicates that nano-cuprous oxide has high selectivity when used for carbon dioxide or carbon monoxide reduction. When the catalyst prepared by this method is used for carbon monoxide or carbon dioxide, it can promote the coupling of carbon-carbon bonds, so that the multi-carbon product has a high Faraday efficiency, that is, high selectivity, ethylene can be close to 45%, and the overall efficiency of multi-carbon is close to 75%.

[0046] 2. The modification method of the copper-based catalyst for electrocatalytic carbon dioxide reduction provided by the present invention, when the copper-based material is a copper sheet or copper foil, when preparing the catalyst, only the surface of the copper-based material reacts to generate the catalyst. When the catalyst performance decreases or is damaged, the surface layer can be easily removed, and the remaining material can be used to quickly prepare the catalyst according to the method of the present invention, without causing waste of raw materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0048] Figure 1 is the Faraday efficiency of the product obtained by reducing CO2 with the copper-based catalyst in Example 2 of the present invention at different potentials (relative to the potential of the reversible hydrogen electrode);

[0049] Figure 2 is the Faraday efficiency of the product obtained by reducing CO2 using polished copper as a catalyst in Example 2 of the present invention at different potentials (relative to the potential of the reversible hydrogen electrode);

[0050] Figure 3 The copper powder raw material of Example 3 of the present invention (Sigmaldrich.com, cas-No.7440-50-8) and the nano-cuprous oxide particles obtained after modification by the present method were used as catalysts respectively, and the catalysts were heated at a constant current of 200 mA·cm -2 Faradaic efficiency of products obtained from CO2 reduction;

[0051] Figure 4 The SEM images of the copper powder raw material in Example 3 of the present invention and the cuprous oxide obtained after modification by the method at different magnifications are shown;

[0052] Figure 5 is the XRD pattern of the catalyst of Example 1 of the present invention;

[0053] Figure 6 is an element distribution diagram of the deposited cuprous chloride obtained in Example 1 of the present invention;

[0054] Figure 7 is an element intensity diagram of deposited cuprous chloride obtained in Example 1 of the present invention;

[0055] Figure 8 is the element distribution diagram of cuprous oxide obtained in Example 1 of the present invention;

[0056] Fig. 9 is an element intensity diagram of cuprous oxide obtained in Example 1 of the present invention;

[0057] Fig.10 is the element distribution diagram of the activated copper obtained in Example 1 of the present invention;

[0058] Fig.11 is an element intensity diagram of activated copper obtained in Example 1 of the present invention;

[0059] Figures 12-14 1 is a SEM image of the copper-based material of Example 1 of the present invention at different stages and different scales during the modification process;

[0060] Fig.15 is a cyclic voltammetry curve of polished copper in Example 2 of the present invention;

[0061] Fig.16 This is a dual capacitance calculation diagram obtained by testing the electrochemically active surface area of ​​polished copper in Example 2 of the present invention;

[0062] Fig.17 is a cyclic voltammetry curve diagram of activated copper in Example 2 of the present invention;

[0063] Fig.18 This is a dual capacitance calculation diagram obtained by testing the electrochemically active surface area of ​​activated copper in Example 2 of the present invention;

[0064] Fig.19 This is a cyclic voltammetry test diagram of polished copper and activated copper in Example 1 of the present invention;

[0065] Fig. 20 is the Auger LMM electron spectrum of cuprous oxide and activated copper in Example 1 of the present invention;

[0066] Fig.21 The ultraviolet photoelectron spectrum (UPS) and work function of the catalyst after 5 hours of cuprous oxide, activated copper and CO2 reduction test in Example 1 of the present invention;

[0067] Fig. 22 This is a flow chart of the modification method of the copper-based catalyst for electrocatalytic carbon dioxide reduction according to Example 1 of the present invention. DETAILED DESCRIPTION

[0068] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0069] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0070] Example 1

[0071] This embodiment provides a modification method for a copper-based catalyst for electrocatalytic carbon dioxide reduction. The flow chart of the modification method is shown in Fig. 22 , including the following steps:

[0072] (1) Weigh 0.298 g NaCl and 0.624 g CuSO4·5H2O respectively, pour into a 100 mL beaker, add deionized water to a volume of 50 mL, and stir until the solution becomes clear and turns light blue, obtaining a mixed solution of 0.1 M NaCl and 0.05 M CuSO4. 2+ and 0.1 M Cl - First solution.

[0073] Weigh 50 g of KHCO3 into a 500 mL volumetric flask, add deionized water to 500 mL to obtain a 1 M KHCO3 solution, and take 20 mL into a 25 mL beaker, which is the second solution.

[0074] (2) Take 80 mL of 85% phosphoric acid solution in a 100 mL beaker and use it as a polishing solution. Place the copper foil in the polishing solution under a two-electrode system, electrolyze at 3V for 60 seconds to polish the copper foil, then clean it and take it out for use; the polished copper foil is bright and has a metallic luster. The size of the copper foil is 0.5 cm × 2.5 cm and the thickness is about 10 μm.

[0075] The copper foil was immersed in the first solution for a few seconds, and the surface color of the copper foil instantly darkened and the color was close to reddish brown, indicating that the surface neutralization reaction had been completed, cuprous chloride was deposited in situ, and a layer of cuprous chloride (CuCl) was obtained on the surface of the copper foil.

[0076] (3) The copper foil taken out in step (2) is quickly transferred to the second solution, and the surface of the copper foil quickly turns yellow, which indicates that nano cuprous oxide particles are formed in situ on the surface of the copper foil.

[0077] Example 2

[0078] This embodiment provides a method for modifying a copper-based catalyst for electrocatalytic carbon dioxide reduction, comprising the following steps:

[0079] (1) Weigh 0.426 g CuCl2·2H2O and pour it into a 100 mL beaker. Add deionized water to a volume of 50 mL and stir until the solution becomes clear and turns blue. This is 0.05 M CuCl2·2H2O. 2+ and 0.1 M Cl - The first solution.

[0080] Weigh 10.0 g KHCO3 into a 1000 mL volumetric flask, add deionized water to 1000 mL to obtain a 0.1 M KHCO3 solution. Take 80 mL into a 100 mL beaker, which is the second solution.

[0081] (2) A copper sheet with a size of 0.5 cm×2.5 cm and a thickness of about 1 mm was used as the copper-based material, and the copper sheet was polished and cleaned according to the method of Example 1.

[0082] The copper sheet was immersed in the first solution for a few seconds, and the surface color of the copper sheet instantly darkened and the color was close to reddish brown, indicating that the surface neutralization reaction had been completed, cuprous chloride was deposited in situ, and a layer of cuprous chloride (CuCl) was obtained on the surface of the copper foil.

[0083] (3) The copper sheet taken out in step (2) is quickly transferred to the second solution, and the surface of the copper foil quickly turns yellow, which indicates that nano cuprous oxide particles are formed in situ on the surface of the copper foil.

[0084] Example 3

[0085] This embodiment provides a method for modifying a copper-based catalyst for electrocatalytic carbon dioxide reduction, comprising the following steps:

[0086] (1) Directly weigh 0.426 g CuCl2·2H2O, pour into a 250 mL reagent bottle, add deionized water to a volume of 50 mL, and stir until the solution becomes clear and turns blue, thus obtaining 0.05 M CuCl2·2H2O. 2+ and 0.1 M Cl - The first solution.

[0087] Weigh 10.0 g KHCO3 into a 1000 mL volumetric flask, add deionized water to 1000 mL to obtain a 0.1 M KHCO3 solution. Take 50 mL into a 250 mL reagent bottle, which is the second solution.

[0088] (2) Copper powder (Sigmaldrich.com, cas-No.7440-50-8) with a diameter of less than 45 μm is added to the first solution under stirring. The color of the solution gradually changes, indicating that most of the copper particles have completed the surface neutralization reaction and formed a layer of cuprous chloride (CuCl). Use a suction filtration device to filter. The filter paper can use a water filter paper with a pore size of 0.45 μm. Rinse it with deionized water, and try not to carry divalent copper ions and halogens into the next step to obtain filter paper with precipitates attached.

[0089] (3) The filter paper of step (2) is immersed in the second solution, and the precipitate is desorbed from the filter paper into the second solution. The color of the second solution gradually changes to yellow, indicating that most of the copper particles have completed the surface reconstruction reaction and nano cuprous oxide particles are prepared.

[0090] Example 4

[0091] This embodiment provides a method for preparing a copper-based catalyst for catalytic reduction, comprising the following steps:

[0092] (1) Weigh 0.426 g CuCl2·2H2O and pour it into a 100 mL beaker. Add deionized water to a volume of 50 mL and stir until the solution becomes clear and turns blue. The concentration is 0.05 M CuCl2·2H2O. 2+ and 0.1 M Cl - The first solution.

[0093] Weigh 56.11 g of KOH into a 1000 mL volumetric flask, add deionized water to 1000 mL to obtain a 1 M KOH solution, take about 10 mL, add water to adjust the pH to 12, and obtain a second solution.

[0094] (2) A copper sheet with a size of 0.5 cm×2.5 cm and a thickness of about 1 mm was used as a copper-based material and polished and cleaned according to Example 1 to obtain a cleaned copper sheet.

[0095] When the copper sheet is placed in the first solution for a few seconds, the surface color of the copper sheet darkens instantly, indicating that the surface neutralization reaction has been completed, cuprous chloride is deposited in situ, and a layer of cuprous chloride (CuCl) is obtained on the surface of the copper sheet.

[0096] (3) The copper sheet obtained in step (2) was quickly immersed in the second solution, and it was observed that the surface of the copper foil quickly turned light yellow, indicating that nano cuprous oxide particles were prepared.

[0097] Comparative Example 1

[0098] This comparative example provides a method for preparing a copper-based catalyst, which uses a reducing agent to reduce cuprous oxide, comprising the following steps:

[0099] Dissolve 0.1g Na3C6H5O7·2H2O in 200mL ultrapure water, and stir the solution for about 25min. Then add 0.5mL CuSO4·5H2O (0.77M) solution to the above solution and stir for about 6min; slowly drip 0.5mL NaOH (4.8M) into the mixed solution at about 30°C; finally, add 0.5mL ascorbic acid solution (1.2M), stir for about 35 minutes, place for aging for about 12h, and centrifuge the solution. Cu2O nanocubes were obtained by centrifugation, and thoroughly washed with ultrapure water and ethanol for 6 times, and dried in a vacuum oven at 40°C to obtain nanocubic cuprous oxide particles. Electrochemical experiments show that the multi-carbon product (C 2+ ) selectivity is 55.9%.

[0100] Test Example 1

[0101] This test example provides the test method and results of the reduction performance of the copper-based catalyst modified by the example, as follows:

[0102] (1) Test method

[0103] ① When the copper-based material is a bulk solid, the test method of the catalyst in each embodiment includes: using an electrochemical workstation (CHI 760E), an Ag / AgCl electrode as a reference electrode (saturated KCl as a filling solution), a platinum sheet as a counter electrode, and the copper catalyst obtained in each embodiment as a working electrode, to perform a CO2 reduction experiment. 1 hour before the reduction experiment, 0.1M KHCO3 was used as an electrolyte, and CO2 gas was introduced until the reduction performance test was completed, with an accurate CO2 gas flow rate of 50.0mL / min.

[0104] Activation of the copper catalyst obtained in each embodiment: A constant potential was applied to the working electrode according to the above method to test the reduction performance. Before the reduction performance test, a voltage of -1.8V vs. Ag / AgCl was applied for activation for 1 min. The material after the copper-based catalyst was activated was recorded as activated copper, and then the reduction performance test was performed.

[0105] ② When the copper-based material is copper powder, the test method of the catalyst in each embodiment includes:

[0106] Preparation of working electrode: 16 mg of cuprous oxide particles were dispersed in 5 mL of isopropanol solution, which contained 200 μL of Nafion solution with a concentration of 5.0 wt%. The catalyst slurry was prepared by ultrasonic treatment. The catalyst slurry was sprayed onto a carbon paper substrate (purchased from Gaoshi Ruilian) using a nitrogen spray gun. The loading amount of the catalyst slurry was 2 mg / cm 2 , dried, and cut to obtain a single electrode with a size of 2 cm×2 cm (the actual use area is 1 cm×1 cm).

[0107] Performance test: The electrochemical measurement was carried out in a two-electrode system in an electrochemical workstation (AutoLab, AutoLab Type: PGSTAT204, Serial no: Aut52703). Nickel foam was used as the anode, 50 ml of 1 M KOH solution was used as the electrolyte, and the working electrode prepared above was used as the cathode. -1 CO2 gas was introduced at a rate of . The performance of the cathode was evaluated by constant current electrolysis.

[0108] (2) Test method for reduction products

[0109] After the reduction performance test experiment was carried out for 60 minutes, the gas phase product was detected by a gas chromatograph (Fuli Instruments GC9790Plus) coupled with a thermal conductivity detector (TCD) and a flame ionization detector (FID), and the liquid phase product was detected by a nuclear magnetic resonance (NMR) spectrometer (Bruker 400MHz), and the Faraday efficiency of the gas phase product and the liquid phase product was calculated.

[0110] Figure 1 is the Faraday efficiency of the product obtained by reducing CO2 with the copper-based catalyst in Example 2 at different potentials (relative to the potential of the reversible hydrogen electrode); Figure 2 The Faraday efficiency of the product obtained by reducing CO2 with polished copper as a catalyst in Example 2 at different potentials (relative to the potential of the reversible hydrogen electrode); wherein the polished copper refers to the copper-based material obtained after polishing and cleaning in step 2. Figure 1 and Figure 2 It can be seen from the results that the cuprous oxide catalyst obtained in Example 2 can significantly improve the catalytic efficiency and product selectivity, and improve the stability and current density of the catalyst.

[0111] Figure 3 The copper powder raw material of Example 3 of the present invention (Sigmaldrich.com, cas-No.7440-50-8) and the nano-cuprous oxide particles obtained after modification by the present method were used as catalysts respectively, and the catalysts were heated at a constant current of 200 mA·cm -2 The Faradaic efficiency of the products obtained by reducing CO2 is Figure 3 It can be seen that the copper powder is modified by the method of the present invention, and the obtained product has a significant improvement in the efficiency of carbon dioxide reduction and a decrease in hydrogen production. Figure 3 Along the horizontal axis, the products correspond to CO, H2, CH4, C2H4, C2H5OH, C3H7OH, CH3COOH, CH3CHO, and HCOOH.

[0112] Figure 4 The SEM images of the copper powder raw material of Example 3 of the present invention and the cuprous oxide obtained after modification by the method are shown in FIG. a and b are SEM images of the copper powder at different magnifications, and c and d are SEM images of cuprous oxide at different magnifications. It can be seen from the figure that after being treated by the method of the present invention, the surface of the copper-based material undergoes a very obvious reconstruction, and the reconstruction effect is very good. The coverage of the nano-cuprous oxide particles on the surface of the copper-based material is extremely high.

[0113] Test Example 2

[0114] This test example provides relevant tests for characterizing the catalyst structure of the embodiment, as follows:

[0115] (1) Figure 5 is the XRD pattern of the catalyst of Example 1; wherein, electropolished copper (Electropolished Cu) refers to the copper-based material after the copper foil of Example 1 is polished; deposited cuprous chloride refers to the cuprous chloride (PrecipitatedCuCl) generated in step (2); cuprous oxide refers to the cuprous oxide catalyst (Original Cu2O) prepared in Example 1; activated copper (ActivatedCu) refers to the material after the cuprous oxide catalyst prepared in Example 1 is activated according to part (1) of Test Example 1.

[0116] Figure 6 1 is the element distribution diagram of the deposited cuprous chloride obtained in Example 1; wherein a is a blank diagram, b is the copper element, c is the oxygen element, and d is the chlorine element. Figure 7 This is the element intensity diagram of the deposited cuprous chloride obtained in Example 1. Figure 8 1 is the element distribution diagram of cuprous oxide obtained in Example 1, a is a blank diagram, b is oxygen element, c is copper element, and d is chlorine element. Fig. 9 This is an element intensity diagram of cuprous oxide obtained in Example 1. Fig.10 1 is the element distribution diagram of the activated copper obtained in Example 1, a is a blank diagram, b is oxygen element, c is copper element, and d is chlorine element; Fig.11 This is the element intensity diagram of activated copper obtained in Example 1.

[0117] It can be seen from the XRD and element distribution diagram that the copper-based material can generate cuprous chloride after reacting with the first solution, and cuprous chloride can generate cuprous oxide after reacting with hydroxide ions. The cuprous oxide catalyst is converted into non-oxidized copper in the bulk phase after activation.

[0118] (2) Figures 12-14 The SEM images of the copper-based material in Example 1 at different stages and scales during the modification process are as follows: Figures 12-14 Figures a and b are SEM images of polished copper, c are SEM images of cuprous oxide, and d are SEM images of activated copper. As can be seen from the figure, cuprous oxide is in the form of cubic particles with many small and irregular pore structures on the surface. Overall, the morphology of cuprous oxide is relatively regular and the distribution is relatively uniform, indicating that cuprous oxide has good performance in reducing CO2 or CO.

[0119] (3) Fig.15 This is the cyclic voltammetry curve of polished copper in Example 2. The arrow directions in the figure correspond to 20 mv·S -1 、40mv·S -1 、60mv·S -1 、80mv·S -1 、100mv·S-1 , Fig.16 is a dual capacitance calculation diagram obtained by testing the electrochemically active surface area of ​​polished copper in Example 2; Fig.17 This is the cyclic voltammetry curve of the activated copper in Example 2. The arrows in the figure correspond to 20 mv·S -1 、40mv·S -1 、60mv·S -1 、80mv·S -1 、100mv·S -1 , Fig.18 This is a dual capacitance calculation diagram obtained from the electrochemical active surface area test of activated copper in Example 2. It can be seen from the figure that the modified copper-based material has a higher electrochemical active surface area and a higher electrochemical reaction activity, and therefore has a stronger ability to reduce carbon dioxide at a higher current density. It also proves that the modified material has a higher roughness and is more conducive to the generation of multi-carbon products.

[0120] (4) Surface structure analysis of the copper foil of Example 1 was performed. Fig.19 This is the cyclic voltammetry test diagram of polished copper and activated copper in Example 1. It can be clearly seen from the figure that the modified copper-based material has a higher current response value under the same conditions, which also proves that this modification method can enhance the electrochemical reaction activity of the copper-based material. More importantly, it can be clearly seen that the peak corresponding to the (100) crystal plane of the modified copper-based material is narrower and stronger, indicating that it has a richer and more regular (100) crystal plane, indicating that it has a stronger role in promoting carbon-carbon bond coupling, greatly increasing the efficiency of carbon dioxide reduction to multi-carbon products.

[0121] (5) Fig. 20 This is the Auger LMM electron spectrum of cuprous oxide and activated copper in Example 1, the left picture is cuprous oxide particles, and the right picture is activated copper; Fig.21 This is the ultraviolet photoelectron spectrum (UPS) and work function of cuprous oxide, activated copper and the catalyst after 5 hours of CO2 reduction test. The left picture is cuprous oxide, the middle picture is activated copper, and the right picture is the catalyst after 5 hours of CO2 reduction test.

[0122] UPS tests the band structure of the catalyst surface, and the work function is the work function. It can be seen from the figure that the work function values ​​before and after activation have significant changes, with the activated copper being 4.21V and the reduction test being 4.18V after 5 hours, indicating that the work function of the material has not changed much after the CO2 reduction test, and the work functions of the activated copper and the catalyst after 5 hours of the test are close, indicating that the band structure of the surface of the cuprous oxide obtained by the modification method of the present invention has not changed substantially after continuous operation for 5 hours, and the catalyst performance is relatively stable.

[0123] Test Example 3

[0124] This test example provides the recyclability of the cuprous oxide prepared in Example 1.

[0125] The CO2 reduction performance was tested according to the method in Experimental Example 1. The C2H4 content in the gas phase was tested by gas chromatography. The CO2 gas flow rate was 20 mL / min. The sample was injected every 20 min to obtain the C2H4 content at that time. The C2H4 content was tested 15 times, which was recorded as one cycle. The process was repeated 57 times, for a total of 57 cycles. The C2H4 test results at 20 min, 40 min, 60 min, 260 min, 280 min and 300 min in each cycle are shown in Table 1.

[0126] The results show that the cuprous oxide catalyst provided by the present invention can be reused without a significant decrease in efficiency, indicating that the catalyst prepared by the method of the present invention has a long service life and has long-term operating stability.

[0127] Table 1 Content of C2H4 (ppm) obtained by cyclic test in Example 1

[0128]

[0129]

[0130]

[0131] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.

Claims

1. A method for modifying a copper-based catalyst for electrocatalytic carbon dioxide reduction, characterized in that: The following steps are involved: (1) preparing a first solution containing copper ions and halogen ions and a second solution containing hydroxide ions respectively and setting them aside; (2) placing a copper-based material into a first solution to react, generating a cuprous halide phase on the surface of the copper-based material, and taking out the copper-based material; (3) The copper-based material taken out in step (2) is placed in the second solution to react and generate cuprous oxide in situ.

2. The modification method according to claim 1, characterized in that There is a zero-valent copper phase on the surface of the copper-based material; Preferably, the copper-based material is copper foil, copper sheet or copper powder; Preferably, the copper powder is at least one of copper nanotubes, copper nanospheres and copper nanorods.

3. The modification method according to claim 2, characterized in that In the step (3), the reaction is carried out until the surface of the copper-based material turns yellow, and cuprous oxide is generated in situ.

4. The modification method according to any one of claims 1 to 3, characterized in that: The halogen ion is at least one of a chloride ion and a bromide ion; Preferably, the first solution includes at least one of a copper salt and a halide, ensuring that the first solution contains both copper ions and halide ions; Preferably, the copper salt is at least one of copper sulfate, copper nitrate, copper chloride and copper bromide; Preferably, the halide is at least one of sodium chloride, potassium chloride, sodium bromide, potassium bromide, copper chloride and copper bromide; Preferably, the first solution is at least one of copper chloride and copper bromide.

5. The modification method according to any one of claims 1 to 4, characterized in that: The second solution includes at least one of a strong base, a weak acid salt and a base, ensuring that the second solution contains hydroxide ions; Preferably, the strong base weak acid salt is at least one of potassium bicarbonate, potassium carbonate, sodium bicarbonate, sodium carbonate, potassium acetate and sodium acetate; Preferably, the base is at least one of sodium hydroxide and potassium hydroxide.

6. The modification method according to claim 5, characterized in that When the second solution is a strong base and a weak acid salt, the concentration of the second solution is 0.01 mol / L to 1 mol / L; Preferably, when the second solution is alkaline, the pH of the second solution is ≥12.

7. The modification method according to any one of claims 1 to 6, characterized in that: The molar ratio of copper ions to halogen ions in the first solution is (1-10):(1-10); Preferably, the concentration of copper ions in the first solution is 0.01 mol / L to 1 mol / L; Preferably, the concentration of halogen ions in the first solution is 0.01 mol / L to 1 mol / L.

8. The copper-based catalyst obtained by the modification method according to any one of claims 1 to 7.

9. A method for catalytic reduction of carbon dioxide, characterized in that: A copper-based catalyst prepared by the modification method according to any one of claims 1 to 7.

10. A method for catalytic reduction of carbon monoxide, characterized in that: A copper-based catalyst prepared by the modification method according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Graded tip cuprous oxide single crystal material as well as preparation method and application thereof

    CN115852485A

  • Gas-assisted synthesis method and application of microcrystalline cuprous oxide electrocatalyst

    CN116005195A

  • Preparation method of CuO-coated Cu2O composite catalyst for electrocatalytic reduction of carbon dioxide into ethylene

    CN116288474A

  • Preparation method of copper-based nano material rich in two-dimensional defects and application of copper-based nano material in electrocatalytic CO2 reduction

    CN116590775A

Cited By

  • Preparation method of Cu foil loaded nano Cu2O electrode and application of Cu foil loaded nano Cu2O electrode in pulse carbon dioxide electrocatalytic reduction

    CN120193296A